Short Communication: Two newly recorded species of Agaricales (Basidiomycota) from Banggai Kepulauan, Sulawesi, Indonesia - ATIK RETNOWATI; ANNE KUSUMAWATY; ISMAIL APANDI; AGUS HARYADI (Society for Indonesian Biodiversity, 2020)
Abstract. Retnowati A, Kusumawaty A, Apandi I, Haryadi A. 2020. Short Communication: Two newly recorded species of Agaricales (Basidiomycota) from Banggai Kepulauan, Sulawesi, Indonesia. Biodiversitas 21: 5615-5621. Two species of Agaricales are reported here as new records for Indonesia, Mycena picta (Fr.) Harmaja (Mycenaceae) and Inocybe stellata E. Horak, Matheny & Desjardin (Inocybaceae). These new records will contribute to the information on mushroom diversity in Indonesia. Mycena picta is characterized by having cylindrical and olive pileus; adnate to slightly decurrent and distant lamellae; filiform, greyish-yellow to dull yellow stipe. Inocybe. stellata is distinguished by having brown conical pileus with squamules surface; adnexed or sinuate and close lamellae with 2 series of lamellulae; terete, glabrous with finely pruinose, base slightly bulbous, light brown stipe; echinulate, globose or subglobose basidiospores; metuloid hymenial cystidia and caulocystidia present. Photographs, descriptions, and line drawings of both macroscopic and microscopic features of the new records are provided herein and give a brief discussion on their taxonomy.